THE INFLUENCE OF INFOGRAPHIC MEDIA USERS ON LEARNING MOTIVATION AND COMPREHENSION OF NEWS TEXTS OF GRADE VII STUDENTS OF SMP HASANUDDIN GOWA - Luli Muliana; A. Rahman Rahim; Rosmini (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to determine the influence of the use of infographic media on the motivation to learn and comprehend news texts of grade VII students of SMP Hasanuddin Gowa. The background of this research departs from the low motivation and ability of students to understand news texts, especially in Indonesian learning which requires students to be able to analyze information critically and systematically. Infographic media was chosen as an alternative because it has attractive visual characteristics, is concise, and is able to present complex information in a more understandable way. The research method used was a pseudo-experiment with a nonequivalent control group design. The research sample consisted of two classes, namely the experimental class that obtained learning using infographic media and the control class that obtained conventional learning. Data collection techniques include learning motivation questionnaires, news text comprehension tests, observations, and documentation. Data analysis was carried out through prerequisite tests (normality and homogeneity), t-test, and MANOVA test to see the effect simultaneously. The results showed that there was a significant difference between the experimental class and the control class on the aspect of learning motivation, where the experimental class had a higher average motivation score after the use of infographic media. In addition, students' understanding of news texts in the experimental class also increased significantly compared to the control class. MANOVA's analysis strengthens the finding that infographic media has a simultaneous effect on students' motivation to learn and comprehension of news texts. Thus, this study concludes that infographic media is effectively used as a learning medium in news text materials. Infographics not only increase students' motivation to learn, but also help students understand the content of the news more comprehensively. These findings recommend the use of innovative visual media in Indonesian learning to improve the quality of students' learning processes and outcomes.